Dialética do Rap: o papel (de) formativo da música no contexto de violência e privação da liberdade de adolescentes infratores - Silva, Fernanda Ortins (2021)
This thesis discusses music’s formative role in the context of violence and deprivation of freedom of teenager offenders. Its goal was to investigate, in the frankfurtian critical theory perspective, how rap, as a cultural practice, can collaborate with the human emancipation or enlarge a heteronomic condition of submission to consume standards conveyed by the cultural industry – concept elaborated by Adorno e Horkheimer (1985) in Dialectics of Enlightenment. This rap is that one more appreciated by teenager offenders during their time of hospitalization, in a socio-educational service center localized in Goiânia and that, for raising several questions among the team, resulted in the follow problem: to what extent can rap, as a cultural practice inserted in the context of adolescents deprived of liberty, dynamize liberating practices or reinforce stigmas and consumption patterns conveyed by the cultural industry? The initial hypothesis was that: even though rap is an artistic-cultural expression that was born from urban black ghettos, as a cultural manifestation, denouncing social ills, injustice and contradictions in society, it was appropriated by the cultural industry, in order to meet a new rationality in transgression. A qualitative-quantitative field research was carried out in a socio-educational care center in Goiânia, whose methodology was divided into three stages: 1) documentary research with music therapy files filled in 2009 and 2010; 2) application of two questionnaires, one with the multidisciplinary team that deals directly with the offending adolescent and the use of music in the unit and another with 14 offending adolescents, seven female and seven male, and 3) semi-structured interview with the internal teenagers. To systematize the data, content analysis was performed, and the categories were constituted according to the critical theory framework of the Frankfurt School. Two raps heard by the juvenile offenders, Sorry Mãe (Fação Central) and Negro Drama (Racionais Mc's), were analyzed in their relationship with the cultural industry, violence, (de)formation, barbarism, education and its potential for emancipation, as basis for content analysis in Adorno's educational and musical perspectives (ADORNO, 1995; 2000; ADORNO; HORKHEIMER, 1985). It was observed, in this research, that the discourse that intends to protest ends up legitimizing the hegemonic interest of the capitalist system, maintaining the status quo and the situation of violence experienced by the juvenile offender, who protests (un)consciously via infraction, in order to satisfy their desires or meet their basic needs, reinforced by the pseudoformation and heteronomy of the individual. The mechanisms of the cultural industry and the dominant society, by the arms ideology, ignore and reinforce violence, barbarism, power, criminality, stereotypes and stigmas historically built on poverty and marginality as being responsible for social violence, appropriating of an (i)rationality, in which barbarism is institutionally resolved through aggressive (de)formative instinctual manifestation. On the other hand, considering education formation as a contradictory, continuous and unfinished process, which can lead to both emancipation and barbarism, rap contains elements that can provoke moments of reflection in the adolescent regarding his current situation.